Screening of Infectious Hypodermal and Haematopoietic Necrosis Virus (IHHNV) infections in wild freshwater prawn, Macrobrachium Rosenbergii, in Malaysia / Hazreen Nita binti Mohd Khalid - Mohd Khalid, Hazreen Nita (2013)
Infectious hypodermal and haematopoietic necrosis virus (IHHNV), so called Penaeus stylirostris densovirus (PstDNV) has been detected widely in penaeid culture facilities in Asia and the Americas. A study by Hsieh et al. (2006) reported that infection of IHHNV on sub-adult and postlarvae of the giant freshwater prawn, Macrobrachium rosenbergii in Southeast Taiwan caused high mortalities of up to 80 %. Eosinophilic intranuclear inclusion bodies were also found on the connective tissues between epithelial cells of the infected samples. In Malaysia, although there is no report of IHHNV infection in M. rosenbergii, preliminary works warrant urgent need to setup a screening protocol for IHHNV for both wild and cultured populations of the species. Studies on screening of IHHNV in giant freshwater prawn were conducted in selected hatchery and wild environment throughout 2009/2010. The purpose of this study was to determine the prevalence of IHHNV in giant freshwater prawn broodstocks in Malaysia by standard polymerase chain reaction (PCR), nested PCR, histopathology and in situ hybridization. PCR screening using standard protocol from OIE was carried out in a prawn hatchery in Perak. Six out of thirty samples (20 %) of random sampling wild berried M. rosenbergii taken directly from Sungai Perak which used as broodstocks in the hatchery were identified as positive with IHHNV infection. Sequence alignment of these positive isolates (389-bp) (GenBank Acc. No. HM536212) in GenBank revealed close identities (98%) to Taiwanese IHHNV strains isolated from M. rosenbergii in Taiwan (GenBank Acc. No. DQ057983). Screening of IHHNV in wild environment were also been conducted where fifty wild-caught giant freshwater prawns were collected monthly (2009/2010) from two selective locations; Sungai Rubana (Perak), and Sungai Timun (Negeri Sembilan). The detection was conducted by nested PCR which based on the iii standard PCR suggested by OIE (OIE, 2003) while for the nested step, newly designed primers were used. Through the year 2009/2010, the prawns captured from Sungai Timun and Sungai Rubana showed positive by nested PCR with prevalence of 64.4 % and 48.7 % respectively. Sequence of positive samples were aligned together with available IHHNV sequences obtained from GenBank and phylogenetic tree was generated which revealed that Malaysia isolates of M. rosenbergii is clustered together with Taiwanese strain (DQ057983). Histopathology examination revealed low intensity of eosinophilic intranuclear inclusion bodies in connective tissues of epithelial cells in hepatopancreas and muscle tissue in some of the samples. An additional method, in situ hybridization (ISH) was also included in the study in order to confirm the findings of histopathology. However, due to lack of positive control of other prawn viruses, this method is unsuccessful to be optimized and further validation cannot be performed. Further investigation in improving this method is necessary as ISH could provide greater diagnosis sensitivity than other conventional histology methods. Results obtained in this study revealed that IHHNV infection were common in adult prawn in both Sungai Rubana and Sungai Timun. The economic impact caused by IHHNV in wild-caught M. rosenbergii was unknown as all the infected samples did not show any mortality. However, the gross sign such as deformity of rostrum and pleopods were seen in the infected prawn. The present study has successfully identified the partial sequence of ORF1 IHHNV genome which leads to the early documentation on the occurrence of IHHNV infection in giant freshwater prawn in Malaysia. To date, there is no definite treatment for this disease, thus frequent screening program of viral disease in prawn should be conducted in order to control the spread of the disease.